Peran Likuiditas dan Financial Distress dalam Mempengaruhi Return Saham: Bukti Empiris pada Sektor Poultry Indonesia - Wahyuni, Komang Tri (widya balina, 2026)
This study aims to analyze the comparison of financial distress levels measured using the Current Ratio (CR) and the Altman Z-Score model and their relationship with stock returns in PT Charoen Pokphand Indonesia Tbk and PT Japfa Comfeed Indonesia Tbk during the period 2020–2025. The research method used is a quantitative approach with a comparative design, and the sampling technique applied is purposive sampling. Data analysis was conducted using descriptive statistics and multiple linear regression.The results indicate that there is no statistically significant difference between the two companies in terms of hal Likuidity (Current Ratio) dan Financial Distress (Altman Z-Score). Descriptively, CPIN has an average Current Ratio of 1.959 and a Z-Score of 3.700, while JPFA shows slightly lower values but remains within the safe zone. Furthermore, regression results reveal that liquidity and financial distress do not have a significant effect on stock returns. Both companies are classified in the safe zone, indicating a healthy financial condition and low risk of financial distress, while stock returns tend to be volatile and influenced by external factors.The study recommends that companies maintain a balance between liquidity, profitability, and capital structure to sustain financial stability. Investors are advised to consider not only financial ratios but also external factors in decision-making. Future researchers are encouraged to expand the sample size and include additional variables to obtain more comprehensive results.